2018
DOI: 10.1111/are.13568
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and size on menthol anaesthesia in Chinese grass shrimp Palaemonetes sinensis (Sollaud, 1911)

Abstract: Chinese grass shrimp, Palaemonetes sinensis (Sollaud, 1911), is an economically important freshwater shrimp in China and adjacent areas. It is advisable to use anaesthesia in this species for certain handling and shipping operations; however, there have been no investigations into the recommended dosages. Here, the influence of five menthol concentrations (varying from 100 to 500 mg/L) on three different size classes of P. sinensis were examined at 8, 12, 16, 20, 24 and 28°C.Induction and recovery times for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Although some research has shown that these environmental factors mght affect eugenol anaesthesia efficiency in fish, these considerations have not yet been explored in crustaceans. Moreover, our previous study demonstrated that menthol dose, water temperature and shrimp size significantly influence anaesthesia and survival rate in P. sinensis 15 .…”
Section: Introductionmentioning
confidence: 94%
“…Although some research has shown that these environmental factors mght affect eugenol anaesthesia efficiency in fish, these considerations have not yet been explored in crustaceans. Moreover, our previous study demonstrated that menthol dose, water temperature and shrimp size significantly influence anaesthesia and survival rate in P. sinensis 15 .…”
Section: Introductionmentioning
confidence: 94%
“…Smaller shrimp have higher rate of anesthetic absorption due to the greater gill surface area in relation to body size (BOWNIK, 2015). Studies on P. sinensis anesthetized with menthol demonstrated a direct relationship between body size and sensitivity to anesthesia (LI et al, 2018a). However, pink shrimp are likely to be more sensitive to EOLA anesthesia than L. vannamei because even the post-larvae forms take a longer time to reach anesthesia (PARODI et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because they are natural products, the application of EOs may be more environmentally friendly and cost-effective (REVERTER et al, 2014). Essential oils have been demonstrated to be safe and effective in studies on Litopenaeus vannamei (PARODI et al, 2012), Macrobrachium rosenbergii (SAYDMOHAMED & PAL, 2009), Palaemonetes sinensis (LI et al, 2018a) and Penaeus monodon (JIANG et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Anesthetic concentration and various biological or environmental factors significantly affect the anesthesia of fish (Santos et al, 2015;Li et al, 2018;Mitjana et al, 2018). Changes in water temperature have been shown to affect induction and recovery time in various fish species (Hamackova et al, 2004;Mylonas et al, 2005;Zahl et al, 2009;Santos et al, 2015;Skår et al, 2017).…”
Section: Discussionmentioning
confidence: 99%